New Zealand : Staff Report for the 2003 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This 2003 Article IV Consultation highlights that despite significant slowdowns in activity in some major overseas markets, New Zealand has maintained a strong pace of economic growth over the past three years. The economy's performance reflected its enhanced flexibility, stemming from the structural reforms of the 1980s and 1990s. After falling sharply in 1999 and 2000, the value of the New Zealand dollar stabilized during 2001, before appreciating substantially in 2002 and into early 2003. The fiscal surplus rose in 2001/02 and is expected to strengthen further over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet